Uncommon oral manifestation of lichen sclerosus: Critical analysis of cases reported from 1957 to 2016 - Tomo, Saygo [UNESP]; Santos, Ingrid-Da Silva [UNESP]; De Queiroz, Sâmia-Alves; Bernabé, Daniel-Galera [UNESP]; Simonato, Luciana-Estevam; Miyahara, Glauco-Issamu [UNESP] (Medicina Oral, S.L., 2017)
Background: Lichen sclerosus is a mucocutaneous autoimmune disease which might be initiated by infectious pathogens as Borrelia Bugrdorferi and HPV. This disease shows destructive potential and is rarely diagnosed in oral mucosa. The purpose of this paper is to evaluate the characteristics of cases described in literature from 1957 to 2016, looking to provide valuable evidence about clinicopathologic features of this disease. Material and Methods: A MedLine search was performed aiming to find oral lichen sclerosus cases in literature and discuss its demographical and pathological characteristics as well as treatment methods performed for these cases. Results: 34 oral lichen sclerosus cases with histological confirmation and one clinicopathologic study linked with this disease were found in literature. Oral lichen sclerosus affected most commonly female patients, were asymptomatic and not associated to skin or genital lesions. Furthermore, affected patients in a range of 7-70-years old (Average age = 31.81). Conclusions: Oral lichen sclerosus is a rare pathologic process with slight predilection for prepubertal girls, for which topical corticosterois have demonstrated satisfactory therapeutic value.
Keywords: Autoimmune diseases; Lichen sclerosus et atrophicous; Mouth; Mouth disease; Skin diseases